Vitamin A deficiency impairs intestinal physical barrier function of fish. Issue 87 (April 2019) - Jiang, Wei-Dan; Zhou, Xiao-Qiu; Zhang, Li; Liu, Yang; Wu, Pei; Jiang, Jun; Kuang, Sheng-Yao; Tang, Ling; Tang, Wu-Neng; Zhang, Yong-An; Shi, He-Qun; Feng, Lin
Abstract: The present study was the first to investigate the effects of dietary vitamin A (VA) on the intestinal physical barrier function associated with oxidation, antioxidant system, apoptosis and cell-cellular tight junction (TJ) in the proximal (PI), mid (MI) and distal (DI) intestines of young grass carp ( Ctenopharyngodon idella ). Fish were fed graded levels of dietary VA for 10 weeks, and then a challenge test using an injection of Aeromonas hydrophila was conducted for 14 days. Results indicated that dietary VA deficiency caused oxidative damage to fish intestine partly by the reduced non-enzymatic antioxidant components glutathione (GSH) and VA contents as well as reduced antioxidant enzyme activities [not including manganese superoxide dismutase (MnSOD)]. Further results observed that the decreased antioxidant enzyme activities by VA deficiency were partly related to the down-regulation of their corresponding mRNA levels which were regulated by the down-regulation of NF-E2-related factor 2 (Nrf2) mRNA levels and up-regulation of kelch-like-ECH-associated protein (Keap1a) (rather than Keap1b ) mRNA levels in three intestinal segments of fish. Meanwhile, VA deficiency up-regulated the mRNA levels of the apoptosis signalling [ caspase-3, caspase-8, caspase-9 (rather than caspase-7 )] associated with the inhibition of the target of rapamycin (TOR) signalling pathway in three intestinal segments of fish. Additionally, VA deficiency decreased the mRNA levels of TJ complexes [ claudin-b, claudin-c, claudin-3, claudin-12, claudin-15a, occludin and zonula occludens-1 (ZO-1) in the PI, MI and DI, as well as claudin-7 and claudin-11a in the MI and DI] linked to the up-regulation of myosin light chain kinase (MLCK) signalling. These results suggested that VA deficiency impaired structural integrity in three intestinal segments of fish. Meanwhile, excessive VA also showed similar negative effects on these indexes. Taken together, the current study firstly demonstrated that VA deficiency impaired physical barrier functions associated with impaired antioxidant capacity, aggravated cell apoptosis and disrupted TJ complexes in the PI, MI and DI, but different segments performed different actions in fish. Based on protecting fish against protein oxidation, the optimal VA levels for grass carp were estimated to be 2622 IU/kg diet. Highlights: Vitamin A deficiency caused fish intestinal cell apoptosis and oxidative damage. Vitamin A deficiency disrupted TJ complexs in different intestinal segments. Vitamin A regulated Nrf2 and MLCK signalling pathways. Effects of vitamin A on fish different intestinal segments are various.